Genomics, proteomics, and vaccines - Grandi, Guido (Wiley, 2004)
While the sequence of the human genome sequence has hit the headlines, extensive exploitation of this for practical applications is still to come.℗¡Genomic and post-genomic technologies applied to viral and bacterial pathogens, which are almost equally important from a scientific perspective, have the potential to be translated into useful products and processes much more rapidly.